Comportamiento productivo de cuyes (Cavia porcellus) de engorde suplementados con tres niveles de butirato de sodio en la dieta - Guzmán G., Isabel (2019)
The aim of this study was to evaluate the effect of dietary supplementation with sodium butyrate (BS) on productive performance in fattening guinea pigs. Fifty 14-21 days old weaned male guinea pigs were randomly distributed in five treatments (0, 100, 200, 300 ppm of BS, 200 ppm of Zn-Bacitracin). Body weight gain, feed consumption and feed conversion were evaluated 70 days after supplementation. No response patterns were detected due to BS or Zn-Bacitracin treatments. It is concluded that, under the experimental conditions, supplementation with BS did not improve the productive parameters evaluated.